Estado democrático de direito, centralidade da pessoa humana e o princípio da adequação setorial negociada na negociação coletiva trabalhista - Clemente, Evellyn Thiciane Macêdo Coêlho (2018)
This dissertation proposes a legal reflection of the mandatory compliance with the limits of the state grant, named by the doctrine of “minimum contract”, in the development of collective bargaining, with applicability of the principle of negotiated sectoral adequacy, which aims to balance working relations and to converge interests related to a democratic and just pacification of labor disputes, before the pillars defended by the Federal Constitution of 1988 of a Democratic State of Law. The objectives of this paper are to meet the fundamentals prescribed in article 3 of the Federal Constitution of 1988, which are to build a free, fair and supportive society; to ensure national development; to eradicate poverty and marginalization and reduce social and regional inequalities; to promote the well-being of all, without prejudice of origin, race, sex, color, age and any other forms of discrimination. The methodological proposal with deductive applicability was based on bibliographical and jurisprudential research, through which a qualitative analysis of the material studied was carried out, with display of the main talking points of the subject on account of the interpretation of the current legislation, in the light of relevant and appropriate theoretical framework. In this context, collective bargaining will not comply with its legal function, in case of permissiveness of fixation of clauses that do not observe the minimum humanistic and social guidelines imposed by the constitutional, international and infraconstitutional legislation. Thus, through the notes, this paper contributed to a concrete demonstration of the importance of the applicability of the Principle of Negotiated Sectoral Adequacy in the practical exercise of collective bargaining in order to avoid regression of the whole solidified foundation in the constitutional and infraconstitutional history of the Law of the Brazilian labor.